Identification of a second Nutlin-3 responsive interaction site in the N-terminal domain of MDM2 using hydrogen/deuterium exchange mass spectrometry - Hernychova, Lenka; Man, Petr; Verma, Chandra; Nicholson, Jude; Sharma, Carrie-Anne; Ruckova, Eva; Teo, Jin Yuan; Ball, Kathryn; Vojtesek, Borek; Hupp, Ted R (Proteomics, 2013)
MDM2 is a multidomain protein that functions as an E3 ubiquitin ligase, transcription repressor, mRNA-binding protein, translation factor, and molecular chaperone. The small molecule Nutlin-3 has been engineered to bind to the N-terminal hydrophobic pocket domain of MDM2. This binding of Nutlin-3 has two consequences: (i) antagonistic effects through competitive disruption of the MDM2-p53 complex and (ii) agonist effects that allosterically stabilize MDM2 protein-protein interactions that increase p53 ubiquitination as well as nucleophosmin deoligomerization. We present a methodology using a hydrogen/deuterium (H/D) exchange platform that measures Nutlin-3 binding to the N-terminal domain of MDM2 (MDM2(1-126)) in order to begin to develop dynamic assays that evaluate MDM2 allostery. In order to localize the regions in MDM2 being suppressed by Nutlin-3, MDM2 was incubated with the ligand and H/D amide exchange was measured after pepsin digestion. One dynamic segment containing amino acids 55-60 exhibited slower deuterium exchange after Nutlin-3 binding, reflecting ligand binding within the hydrophobic pocket. However, another dominant suppression of H/D exchange was observed in a motif from amino acids 103-107 that reflects surface hydrophobic residues surrounding the hydrophobic pocket of MDM2. In order to explore the consequences of this latter Nutlin-3 interaction site on MDM2, the Y104G and L107G mutant series was constructed. The MDM2(Y104G) and MDM2(L107G) mutants were fully active in p53 binding. However, the authentic p53-derived peptide:MDM2(Y104G) complex exhibited partial resistance to Nutlin-3 inhibition, while the p53-mimetic 12.1 peptide:MDM2(Y104G) complex retained normal Nutlin-3 responsiveness. These data reveal the existence of a second functional Nutlin-3-binding site in a surface hydrophobic patch of MDM2, flanking the hydrophobic pocket. This reveals two modes of peptide binding by MDM2 and highlights the utility of H/D exchange as an assay for measuring allosteric effects in MDM2.
Keywords: Allosteric Site; Peptide Fragments; Amino Acid Sequence; lidé; piperaziny; Proto-Oncogene Proteins c-mdm2; Deuterium Exchange Measurement; protoonkogenní proteiny c-mdm2; Molecular Sequence Data; peptidové fragmenty; Imidazoles; Models, Molecular; vodík-deuteriová výměna; imidazoly; sekvence aminokyselin; molekulární sekvence - údaje; Humans; alosterické místo; Piperazines; molekulární modely